2016
DOI: 10.1073/pnas.1608221113
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma bruceimetabolite indolepyruvate decreases HIF-1α and glycolysis in macrophages as a mechanism of innate immune evasion

Abstract: The parasite Trypanasoma brucei causes African trypanosomiasis, known as sleeping sickness in humans and nagana in domestic animals. These diseases are a major burden in the 36 sub-Saharan African countries where the tsetse fly vector is endemic. Untreated trypanosomiasis is fatal and the current treatments are stagedependent and can be problematic during the meningoencephalitic stage, where no new therapies have been developed in recent years and the current drugs have a low therapeutic index. There is a need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 56 publications
2
76
0
Order By: Relevance
“…Additionally, several studies reported that products of aromatic amino-acid metabolism were increased in urine and blood of animals infected with T. b. gambiense and T. b. evansi [ 233 , 234 , 235 ]. Furthermore, it has been demonstrated that indolepyruvate can modulate the immune response in infected mice [ 236 ], which points to a role for aromatic amino acids in the successful establishment of an infection by T. brucei .…”
Section: Amino Acid Metabolism In Tritrypsmentioning
confidence: 99%
“…Additionally, several studies reported that products of aromatic amino-acid metabolism were increased in urine and blood of animals infected with T. b. gambiense and T. b. evansi [ 233 , 234 , 235 ]. Furthermore, it has been demonstrated that indolepyruvate can modulate the immune response in infected mice [ 236 ], which points to a role for aromatic amino acids in the successful establishment of an infection by T. brucei .…”
Section: Amino Acid Metabolism In Tritrypsmentioning
confidence: 99%
“…For example, they increase uptake of triglycerides via the CD36 receptor for use in fatty acid oxidation [ 7 ]. Recently it has been found that pathogen generated substrates such as butyrate or indolepyruvate promote an anti-inflammatory phenotype [ 8 , 9 ]. In the context of immune-tumour interactions, tumour associated macrophages reduce glucose availability and promote the formation of an organized tumor vasculature [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…IPA is synthesized by the action of aromatic amino acid transaminases. In addition, some microorganisms produce IPA by the deamination of tryptophan (19,20). IPA reduced damage in the striatum after transient forebrain ischemia in the rat (21).…”
mentioning
confidence: 99%